Criminal Law Reform as an Effort to Enforce the Law on the Crime of Prostitution - Ayu Larasati (Jurnal Ilmiah Hukum dan Keadilan, 2026)
Prostitution in Indonesia remains a significant social and legal problem, as it violates both moral and legal norms. This study employs a normative juridical approach to examine the regulation and enforcement of laws related to prostitution. The findings indicate that, although existing legislation primarily targets service providers, comprehensive criminal law reform is necessary to address all parties involved, including intermediaries (pimps), sex workers, and clients. Effective regulation should combine criminal penalties, rehabilitation programs, and vocational training to support sex workers in transitioning to alternative livelihoods. The study concludes that legal reforms are essential to establish a deterrent effect, prevent the recurrence of prostitution, and promote justice, thereby contributing to the eradication of prostitution in Indonesia.